Fault geometry and rupture speed as controls on off-fault deformation in the 2023 Turkey-Syria earthquakes - Xi Xi; Chenglong Li; Tao Li; Zhanyu Wei; Zhangfeng Ma; Guohong Zhang; Chunyan Qu; Honglin He; Xinjian Shan (Communications Earth & Environment, 2025)
Abstract Coseismic off-fault deformation (OFD) measurements provide crucial insight into fault deformation behavior and shallow faulting damage. Although kinematic and dynamic characteristics of the causative faults associated with the 2023 Turkey-Syria earthquake doublet (Mw 7.8 and 7.6) were well determined, the OFD behavior and mechanism remain poorly constrained. Here we utilized high-resolution optical satellite geodesy to illuminate OFD distribution of the earthquake doublet. We found an average of ~80% and ~83% of coseismic fault deformation were localized on the primary fault planes of the Mw 7.8 and Mw 7.6 earthquakes, respectively; together, the remaining deformation manifested as OFD distributed within an average of 200-m- and 140-m-wide damage zones. Our observations revealed the OFD systematically increases in fault segments that have more complex geometry and slower coseismic rupture velocity, validating that both factors exhibit a significant facilitation on first-order variation of OFD during the earthquake doublet.